Design, Construction and Instrumentation of Photobioreactor for Microalgae - Jesús Alberto Coronado-Reyes; Juan Carlos González-Hernández (Brazilian Archives of Biology and Technology)
Abstract The cultivation of microalgae has been a biotechnological technique with many advances throughout history; however, depending on the growth conditions, the production of carbohydrates, proteins, lipids, vitamins, polyphenols and terpenes (metabolites primary and secondary) has been favored or affected. This work consists of designing and building a photobioreactor with internal blue LED light to monitor the pH, temperature, carbon dioxide (CO2) concentration and light intensity in real time to increase the current production yields of biomass and metabolites with great potential for biotechnological applications. With the construction of the photobioreactor, the growth kinetics of the microalgae C. vulgaris were determined by applying the Taguchi experimental statistical methodology (mixotrophic medium) to evaluate its antioxidant activity. Like independent variables: substrate concentration (sodium nitrate, NaNO3) and light exposure time (photoperiod). The dependent variables were as follows: cell growth, biomass, substrate consumption (UV‒vis, 301 λ), and metabolites with antioxidant activity (ABTS•+ and DPPH• radical methods). In conclusion, the construction of a photobioreactor for microalgae cultivation allows greater control of growth factors such as CO2, pH, temperature and dissolved O2 and allows the microalgae growth medium to be isolated from the outside and thus avoid contamination by microbial agents from the environment. Similarly, the best growth condition for C. vulgaris with antioxidant activity is a concentration of 3.6 mM NaNO3 and a low photoperiod time of 8 hours of light and 16 hours of darkness, generating an equivalent response of Trolox 16 µM/mL for ABTS•+ and equivalents of Trolox 6 µM/mL for DPPH•.